Determinant return to work program for work-injured employees in Indonesia - Aprianto, Dwi; Hakim, Dedi Budiman; Sahara, Sahara (Publisher of Widyagama University of Malang (UWG Press), 2023)
Work accidents can determine the safety quality in the workplace, which contributes to national economic development. It is estimated that GDP losses from work injuries are 3.94% annually. It is important to reactivate work-injured persons to be productive. The Return To Work (RTW) program was formed to accommodate employees who become disabled after a fatal injury. This study aims to estimate the RTW rate and the factors that influence the probability of success of the RTW Program for work-injured persons. Data were obtained from Social Security Organization (BPJS Ketenagakerjaan) from 2020-2021, with 195 participants following this program due to fatal work injuries. This study is cross-sectional and uses a logistic regression model. The result is 75.90% of participants could work after following this program. The factor positively influences the success of the RTW program, such as lower and upper amputation (OR=2.474), working in the secondary sector (OR=2.409), following the RTW program in 2020 (OR=2.184), and paying a lower insurance premium rate (OR=3.260). The rate of the RTW in Indonesia is relatively high, with more than three-quarters of participants able to work. Risky groups need more attention by providing information about the work environment and road hazards. This finding can be a reference for developing the RTW program to increase the assistance to high-risk patients for not able to work after the RTW program.JEL Classification E24; H55; J24